Assessment of quality of care among in-patients with postpartum haemorrhage and severe pre-eclampsia at st. Francis hospital nsambya: a criteria-based audit. Issue 1 (December 2017) - Lumala, Alfred; Sekweyama, Peter; Abaasa, Andrew; Lwanga, Humphrey; Byaruhanga, Romano
Abstract Background The maternal mortality ratio of Uganda is still high and the leading causes of maternal mortality are postpartum haemorrhage (PPH), severe pre-eclampsia and eclampsia. Criteria-based audit (CBA) is a way of improving quality of care that has not been commonly used in low income countries. This study aimed at finding out the quality of care provided to patients with these conditions and to find out if the implementation of recommendations from the audit cycle resulted in improvement in quality of care. Methods This study was a CBA following a time series study design. It was done in St. Francis Hospital Nsambya and it involved assessment of adherence to standards of care for PPH, severe pre-eclampsia and eclampsia. An initial audit was done for 3 consecutive months, then findings were presented to health workers and recommendations made; we implemented the recommendations in a subsequent month and this comprised three interventions namely continuing medical education (CME), drills and displaying guidelines; a re-audit was done in the proceeding 3 consecutive months and analysis compared adherence rates of the initial audit with those of the re-audit. Results Pearson Chi-Square test revealed that the adherence rates of 7 out of 10 standards of care for severe pre-eclampsia/eclampsia were statistically significantly higher in the re-audit than in the initial audit; also, the adherence rates of 3 out of 4 standards of care for PPH were statistically significantly higher in the re-audit than in the initial audit. Conclusion The giving of feedback on quality of care and the implementation of recommendations made during the CBA including CME, drills and displaying guidelines was associated with improvements in the quality of care for patients with PPH, severe pre-eclampsia and eclampsia.